PERBANDINGAN KADAR ENZIM KREATININ FOSFOKINASE DAN NYERI OTOT SEBELUM DAN SESUDAH LATIHAN BERENANG SELAMA EMPAT MINGGU PADA PERENANG UNIT KEGIATAN MAHASISWA KLUB RENANG - Nur Akmal; Reni Farenia; Delita Prihatni (PAIFORI, 2020)
A research has been done to compare the differences on the enzyme creatine phosphokinase (CPK) level and muscle soreness before and after 4-weeks swim practices on swimmers of College swimming club. Eighteen healthy male swimmers (mean ± SD; age: 19,94 ± 1,86 years; weight: 65,28 ± 6,14 kg; height: 1,72 ± 0,43 m) participated in this study. All subjects performed their 4-weeks swim practices which consist of 2x120 hours per week with 500 meters average daily swim distance and weight training. Blood was collected before and after the practices and CPK were analyzed. Questionnaires concerning muscle soreness were filled put before each blood draw. Results were analyzed using normality test and Wilcoxon signed rank test (p<0.05). There was significant increase in CPK level during 4-weeks swim practices by 59.41% (p=0.044). Whereas for muscle soreness (overall and specifically in arms and thighs), there was no significant differences between before and after the 4-weeks swim practices. As a conclusion, participation in 4-weeks swim practices resulted in significant serum CPK enzyme elevation, but there was lack of significance in muscle soreness differences on swimmers of College swimming club.